Inovação no transporte público: um estudo sobre bilhetagem eletrônica - Lubeck, Rafael Mendes (2011)
The concept of innovation was highlighted and spread during the 20th century under the theoretical framework of theories of economic development, and gradually gained importance as innovation in management, process and product lent positive effects to the economic development of nations, institutions and companies. Considering the increased complexity in the competitive landscape, innovation is the keyword of the post-industrial era, and in order to be achieved by the enterprises, it requires new strategies, capabilities and competencies. In the public transportation sector of Rio Grande do Sul, the impacts of both changes in the market dynamics and emergence of new technologies were felt in the changing demands of passengers and in enhanced requirements by service users and by the (government) concession granting authority. These changes allow us to infer the growing need to gain operational efficiency and effectiveness in an industry that used to show a relatively stable situation. Gaining efficiency in public transport operations becomes the key issue for the carriers. However, how to qualify transactions, and reduce existing inefficiencies? In view of the demands of urban and intercity passenger carriers, an electronic-ticketing system was developed in order to control tickets sale, purchase and use.. This system helps the effective control of operations, improving the management of information and allowing the public transport companies to obtain more accurate data and a more efficient and effective management. This study included analysis of improvements achieved with the implementation of the e-ticketing system in the cities of Rio Grande do Sul categorized as cases α, β, and γ, and it aimed to ascertain whether the improvements in the management of the information provided by electronic ticketing qualify it as an innovation. We collected qualitative data through interviews and document analysis. Collected information was analyzed using content analysis and secondary data was used regarding the amount of vehicles and passengers in the cities covered by the survey. It was found that the characteristic effects of an innovation are in line with the results of e-ticketing in the cases analyzed, making this system a way to achieve innovation. In accordance with the directions set for this work, it is worth emphasizing that it was the impacts of the e-ticketing system that were considered innovative and not the system per se, because the electronic billing is a means to achieve innovation and not an innovation in itself.